Beyond tokenism: community-based advocacy and participation in rural WASH governance - Justino Da silva; Daniel D Kameo; Royke R Siahainenia (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study examines community-based advocacy in rural Water, Sanitation, and Hygiene (WASH) governance across two administrative posts in Timor-Leste's Manufahi Municipality. While existing scholarship often frames community participation as inherently empowering, it overlooks how participatory advocacy can simultaneously reproduce local inequalities through elite capture and weak accountability mechanisms. Using a descriptive qualitative approach drawing on interviews, document analysis, and participant observation with ten key informants, the study finds that CBA strengthened community water management groups, revitalized Tara Bandu customary practices, expanded NGO partnerships, and raised public awareness. However, decision-making authority and resource control frequently remained concentrated among local elites and customary power holders. Applying Arnstein's (1969) ladder of participation, community engagement operated largely at the Partnership level, with limited Citizen Control. Participation was often tokenistic: women, youth, and marginalized households were consulted but exercised little influence over financial management, infrastructure prioritization, and enforcement decisions. The study concludes that community-based advocacy alone does not guarantee equitable rural water governance in structurally unequal contexts. Sustainable rural water systems require not only community participation but also formalized social accountability mechanisms, transparent resource governance, and explicit equity safeguards within grassroots institutions.